Awareness of Copyright Infringement Among Undergraduates of The State Universities in Sri Lanka - Saujan, Iqbal, Mr. (UI Scholars Hub, 2023)
Abstract Copyright infringement is known as the use of copyrighted works without the permission of the creators, copyright holders or authors. It is a form of dishonesty and a violation of the authors' economic and exclusive rights. In general, copyright infringement activities have taken place in various ways such as theft, piracy, reuse and plagiarism among students pursuing degree programmes in higher education institutions in Sri Lanka. In this backdrop, this study aims to examine awareness of copyright infringement among students pursuing undergraduate degree programmes at state universities in Sri Lanka. The primary and secondary data have been used in the study. The primary data were collected by Self-Administered Questionnaires (SAQ) distributed to 356 of the selected participants. Selected students are continuing their education in 2016/2017, 2017/2018, 2018/2019 and 2019/2020, including general and honours degree programmes. The samples were selected based on Random Sampling Method (RSM). All received questionnaires were analysed in a descriptive way with the help of SPSS (Version-26) and the results were presented by illustrating in the form of tables. According to the results, it was found that 58.1% of participants were not aware that copyright infringement as an academic dishonesty, as well as copyright law (Intellectual Property Act No.36 of 2003) which is enforced by Sri Lankan government in order to protect intellectual properties. 77.4% of the participants proved that copyright infringement is a kind of prohibited act in their own religion (Islam, Buddhism, Christianity and Hinduism). Moreover, the main factors that lead to copyright infringement of study samples were a lack of awareness of copyright law (38%), the high cost of textbooks (64.6%), and the fear of having low greats in semester examinations (77.4%). The findings of present study would be important to stimulate academics, library personnel, university officials, and policymakers to think of ways to prevent the students from engaging in copyright infringements in future. Moreover, it is a firm belief of the researchers that findings of this study could be a remarkable starting point for future researchers.